2017
DOI: 10.3389/fnins.2017.00421
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Prosthetic Interfaces: Combining Nerve Transfers and Implantable Multichannel EMG Technology to Decode Spinal Motor Neuron Activity

Abstract: Modern robotic hands/upper limbs may replace multiple degrees of freedom of extremity function. However, their intuitive use requires a high number of control signals, which current man-machine interfaces do not provide. Here, we discuss a broadband control interface that combines targeted muscle reinnervation, implantable multichannel electromyographic sensors, and advanced decoding to address the increasing capabilities of modern robotic limbs. With targeted muscle reinnervation, nerves that have lost their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 58 publications
(83 reference statements)
0
31
0
4
Order By: Relevance
“…These few motor axons may then be used to re-innervate a free muscle transplant transferred to the patient s arm, which will not have the functional capacity or power of a biological muscle but instead serve as an additional EMG signal for future prosthetic control (given that a sufficient number of axons regenerate into the transferred muscle target). Since the dexterity of prosthetic control increases with the number of available EMG signals [18,19], free functional muscle transfers have previously been used to increase the number of these muscle signals [16].…”
Section: Introductionmentioning
confidence: 99%
“…These few motor axons may then be used to re-innervate a free muscle transplant transferred to the patient s arm, which will not have the functional capacity or power of a biological muscle but instead serve as an additional EMG signal for future prosthetic control (given that a sufficient number of axons regenerate into the transferred muscle target). Since the dexterity of prosthetic control increases with the number of available EMG signals [18,19], free functional muscle transfers have previously been used to increase the number of these muscle signals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies indicate substantial changes within the motor unit, so far, the effects of such a “high capacity” donor nerve transfer remain mainly unknown . Kuiken et al found a hyperreinnervation of the muscle after TMR procedure, leading to enhanced axonal input of motoneurons.…”
Section: Targeted Muscle Reinnervationmentioning
confidence: 99%
“…Muceli et al showed promising results with an implantable multichannel electrode, which is also capable of recording down to single motor units in combination with all the benefits of implantable devices. Further research will reveal possible implementation, although demand is granted …”
Section: Prosthetic Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Since its introduction in the 1940s, the standard approach to interfacing is the use of few muscle-control signals recorded by surface EMG electrodes (Bergmeister et al, 2017). With this classic approach, two signals are used to control multiple degrees of freedom, often resulting in non-intuitive control (Farina and Aszmann, 2014).…”
Section: Introductionmentioning
confidence: 99%